2021
DOI: 10.1029/2021gl093419
|View full text |Cite
|
Sign up to set email alerts
|

A Single‐Year Cosmic Ray Event at 5410 BCE Registered in 14C of Tree Rings

Abstract: The cosmic-ray flux into the Earth atmosphere fluctuates over time due to various factors. Solar and geomagnetic modulation of galactic cosmic rays are dominating this process on timescales from a few-days to millions of years, such as Forbush decreases (a shielding of galactic cosmic rays due to a coronal mass ejection), the 11-year Schwabe cycle, multidecadal variation such as Grand Solar Minima, or millennial variations in Earth's magnetic field strength. In addition to these recurring factors, sporadic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 44 publications
1
32
2
Order By: Relevance
“…So far, three strong SEP events that led to an abrupt increase of about 1% or more in atmospheric 14 C concentrations within less than two years have been unambiguously detected over the past 3000 years in tree-rings and confirmed with other cosmogenic radionuclides ( 10 Be, 36 Cl) in ice cores, in the years 993 CE, 775 CE and 660 BCE 13,14,19,20 . More, weaker, yet unconfirmed SEP events have been found in the radionuclide records 17,[21][22][23] . They are currently considered candidate events either because there is insufficient data coverage and precision to clearly distinguish them from normal solar modulation or because they have not yet been confirmed 24 .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…So far, three strong SEP events that led to an abrupt increase of about 1% or more in atmospheric 14 C concentrations within less than two years have been unambiguously detected over the past 3000 years in tree-rings and confirmed with other cosmogenic radionuclides ( 10 Be, 36 Cl) in ice cores, in the years 993 CE, 775 CE and 660 BCE 13,14,19,20 . More, weaker, yet unconfirmed SEP events have been found in the radionuclide records 17,[21][22][23] . They are currently considered candidate events either because there is insufficient data coverage and precision to clearly distinguish them from normal solar modulation or because they have not yet been confirmed 24 .…”
Section: Introductionmentioning
confidence: 94%
“…(b) Distribution of the simulated ∆ 14 C increases (blue bars) with a Gaussian fit (dashed line). (c) Distribution of excess 14 C production (blue bars) with Gaussian fit (dashed line).Data Sources: 5410 BCE: Miyake et al 23 , 660 BCE: Sakurai et al 13 , 775 CE and 993 CE: Büntgen et al 48 , 1052 CE and 1279 CE: Brehm et al 17 . Supplementary Fig.…”
Section: Competing Interestmentioning
confidence: 99%
“…After the exciting discovery of the extreme SPEs occurring during the recent Sun's past, it is time to study the phenomenon in detail, in particular, collecting statistic and covering long periods with high-quality data in different cosmogenic isotopes, with a special focus on 36 Cl and 10 Be measured in polar ice cores. The recent works by Miyake et al (2021) and Brehm et al (2021) form the cornerstone for the process of paving a way to detect a larger number of smaller events in the proximity of the sensitivity threshold for the cosmogenic isotope method leading to a breakthrough in our understanding of extreme solar eruptive events and their potential impact on the Earth's environment and our society. In particular, the new result by Miyake et al (2021) would imply, if independently confirmed, that the extreme SPEs are not manifestations of unknown phenomena but rather high-energy/low-probability tail of the "regular" SPE distribution, making it possible to study them in greater details.…”
Section: Discussionmentioning
confidence: 99%
“…factor 25-30 stronger than that of 1956. In the work by Miyake et al (2021), another spike in  14 C has been identified corresponding to the year 5410 BCE. It was about one half of the 775 CE event and a factor of  30 as strong as the one of 1956.…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
See 1 more Smart Citation